The effect of solvent type and extract concentration of Caulerpa racemosa on its antibacterial activity against acne-causing bacteria: The effect of solvent type and extract concentration of Caulerpa racemosa on its antibacterial activity against acne-causing bacteria - Ferdinandus, Meske; Moniharapon, Trijunianto; Setha, Beni (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Acne is a common skin disorder, particularly among adolescents and young adults, with Cutibacterium acnes and Staphylococcus aureus being the main causative bacteria. Conventional antibiotic treatments often lead to resistance, highlighting the need for natural alternatives to antibiotics. This study aimed to determine the effectiveness of Caulerpa racemosa extract as an antibacterial agent against C. acnes and S. aureus, the primary acne-causing bacteria, with a particular focus on the influence of solvent type (methanol and ethyl acetate) and solvent concentration (95%, 75%, 55%, and 35%) on the resulting antimicrobial activity. The extracts were prepared by maceration and screened for phytochemical constituents. The antibacterial activity was tested using the Kirby-Bauer disc diffusion method. The results showed that the methanol extract produced higher yields and greater inhibition zones compared to ethyl acetate, averaging 12.63 mm against C. acnes and 12.94 mm against S. aureus. The bacterial inhibition zone increased significantly with an increase in the extract concentration, and at a concentration of 95%, the inhibition zone reached 15.37 mm against C. acnes and 14.12 mm against S. aureus. Phytochemical analysis revealed the presence of flavonoids, phenolics, tannins, saponins, alkaloids, terpenoids, and steroids, which contributed to the antibacterial activity. This study concludes that C. racemosa, particularly its methanol extract, exhibits significant potential as a natural source of active compounds for topical anti-acne formulations and may serve as a safe alternative to conventional antibiotics in addressing bacterial resistance.